Peers as an Educational Microsystem and Their Influence on the Formation of Student’s Morality - Reksiana Reksiana; Eka Naelia Rahmah; Lintang Awalia Rahayu (STAI Hubbulwathan Duri, 2023)
Peers as a social environment for learning to adjust to group standards, learning to share feelings, be sportsmanlike, learning to accept, and carrying out responsibilities. The purpose of this research is to find out and describe the influence of peers in shaping the morality of students. The method in this study used qualitative research with descriptive research types. The data sources are one school principal, two teachers, and four students. The instruments used are observation, interviews, and documentation. Data analysis techniques include data collection, reduction, presentation, and conclusion. The results of this study indicate that activities that can influence peers in shaping student’s morality include teaching and learning activities in the classroom, religious activities such as Duha prayers in congregation, memorizing of the Qur'an, and religious lectures on certain days. Peers can also provide positive outcomes for students, such as providing new information, social support, and motivation. This is because peer relations are reciprocal, helping each other, trusting each other, loving each other, and complementing each other to form a positive character or good morals for students.